Be myself experiences of the post-90s of Chinese international students in Canadian universities - Nan, Ma (My University, 2016)
This research aims to understand the experiences of a new generation of Chinese international students in Canadian universities and the role of their identities in shaping such experiences, including their resistance toward stereotypes. Data was collected through semi-structural, in-depth interviews with eight international students who were studying at universities in Southern Ontario, were from mainland China and were born during 1990s. The study leads to several major findings. First, these students did not necessarily internalize stereotypes about Chinese international students, China and Chinese culture from other groups, producing from lack of culture exchange, language barrier, cultural difference and the biased mass media, and that they also made their efforts to change this situation. Second, participants appeared to have different relationships with three groups in Chinese student communities. Third, informal support from individual social network was perceived much more effective than formal services on campus. Fourth, they viewed challenges they had experienced as a process of growth, and advanced technology and globalization also helped them to better adapt to the new environment. Across these findings, there is a dynamic relationship between these students’ experiences in Canadian universities and their identities in relation to their national, ethno-cultural, generational and international backgrounds. Although their generally positive and critical thinking on their experiences of studying abroad is related to their generation-related resources, common challenges they collectively encountered also indicate the importance of accessible institutional support.
Keywords: Chinese international students; identity; experiences; services